Changing Higher Education Policies: From the Deistitutionalization to the Reinstitutionalization of the Research Mission in Polish Universities - Kwiek, Marek (My University, 2012)
This paper analyzes changing higher education policies in Poland in the last two decades. It argues that top Polish public universities became divided, with different individual academic and institutional trajectories in the academic fields in which educational expansion occurred (social sciences) and in fields in which it was much less pronounced (natural sciences). Using the concepts drawn from new institutionalism in organizational studies, this paper views the 1990s as the period of the deinstitutionalization of traditional academic rules and norms in public universities, with growing uncertainty about the core of the academic identity. In the expansion era (1990–2005), prestigious public research universities became excessively teaching-oriented. In the period of educational contraction, their currently teaching-oriented segments are expected to become research-intensive. New legislation grounded in an instrumental view of higher education is interpreted as a return to a traditional academic normative consensus, with increased emphasis on, and funding for, the research mission.
Keywords: Polish universities; Poland; Polish higher education; higher education reforms; educational reforms; academic fields; academic profession; tuition fees; cost-sharing; private higher education; public-private; fee-paying tracks; knowledge production; academic articles; Central Europe; Czech Republic; Slovakia; Hungary; Central Europe; Eastern Europe; communism; postcommunism; professorships; academic degrees; institutionalism; institutional approach; normative institutionalism; Johan P. Olsen; institutionalization; deinstitutionalization; reinstitutionalization; research mission; academic productivity; research productivity; research output; internationalization; international visibility; organizational studies; university as institution; institutions; reforming institutions; multiple-employment; private sector; divided institutions; hard and soft fields; teaching-oriented; teaching-focused; normative vacuum; normative consensus; public policy; higher edcuation policy